Place of the victim in records of violence against children - Stevković Ljiljana (Temida, 2012)
The possibility of identifying the scope, prevalence and incidence of violence against children, at the national and international level, is determined by the way of measurement and the kind of information available on this type of crime. The starting point for successful preventive and combative measures of victimization of children is an efficient system of recording and presenting the data on violence to which they are exposed to, based on the information from the incident, the family, the perpetrator and the victim. This paper aims to identify and analyze ways of recording and the type of available data on violence against children, as well as the place of child victim in the officially presented data at the global and national level. In doing so, the paper was based on the research of relevant international and national literature in the field of judicial and social protection statistics, publications based on data from the judiciary, those based on the use of victimization surveys and other prospective or retrospective research of violent victimization experiences in childhood. At the very least an analysis of the Serbian approach to this area is given. [PR Projekat Ministarstva nauke Republike Srbije, br. 179044: Razvoj metodologije evidentiranja kriminaliteta kao osnova kreiranja efikasnih mera za njegovo suzbijanje i br. 47011: Kriminal u Srbiji - fenomenologija, rizici i mogućnosti socijalne intervencije]